Advanced fibrous composite materials for ballistic protection - Chen, Xiaogang (Woodhead Publishing series in composites science and engineering, 2016)
With contributions from leading experts in the field, this cutting-edge book presents some of the most recent developments in the design and engineering of woven fabrics and their use as layering materials to form composite structures for ballistic personal protection. --